Flexural capacity model for RC beams strengthened with bolted side-plates incorporating both partial longitudinal and transverse interactions. (1st August 2018) - Shan, Z.W.; Su, R.K.L.
Highlights: A simplified flexural design method for BSP beams is developed. Effects of partial transverse interaction on longitudinal strain slip are quantified. Moment capacity equations are modified to incorporate the effects of partial interactions. Abstract: Existing reinforced concrete (RC) beams with inadequate flexural capacity can be strengthened by bolting steel plates onto both sides of the face of beam. However, the effectiveness of these bolted side-plated (BSP) beams is affected by the mechanical slipping of bolts which is known as the partial interaction of the steel plates and the RC beam. To avoid overestimating the flexural capacity of the strengthened beam, the effects of partial interaction should be properly quantified in the structural design. Therefore, a new design model to determine the flexural capacity of BSP beams that takes into consideration both partial longitudinal and transverse interactions has been developed in this study. Strain and curvature factors are introduced to quantify the partial interaction. Based on these two factors, modified moment capacity equations are presented. The proposed model is then validated by comparing the analytical results with the test results from another study. Finally, a simplified design method is proposed based on the results of a parametric study.